PENGARUH ETIKA BISNIS, KOMPETENSI INTI DAN STRATEGI KEWIRAUSAHAAN TERHADAP KEUNGGULAN BERSAING DAN KINERJA USAHA PADA PERUSAHAAN TEKNOLOGI INFORMASI JAWA TIMUR - Nursaid, Nursaid (Universitas Muhammadiyah Jember, 2017)
ABSTRACTThis study aims to determine the influence of business ethics, core competence, and entrepreneurial strategy to competitive advantage and business performance at Information Technology Company in East Java. The population of this study is all information technology companies engaged in the field of assembly services, sales and services registered APKOMINDO East Javan is 250 entrepreneurs. The sample in this study is the entire population used as a sample. Validity test and reliability test are used to measure the questionnaire. SEM analysis is used to determine the effect of independent variables on the dependent variable. The results showed that business ethics had no significant effect on competitive advantage but had a significant effect on business performance. Core competence has a significant effect on competitive advantage and business performance. Entrepreneurial strategy has a significant effect on competitive advantage and business performance. Competitive advantage significantly influence business performance at Information Technology company in East Java.Keywords: Business Ethics, Core Competencies, Entrepreneurship Strategies, Competitive Advantages, and Business Performance.